The search for truth: Filming the battle of Meewah - Maddock, Daniel; Baguley, Margaret; Kerby, Martin; Bedford, Alison (Historical encounters, 2023)
The Battle of Meewah (One Tree Hill) was fought just outside the city of Toowoomba in September 1843. The battle constituted the first major setback to European settlement in Queensland, though it slowed rather than halted the dispossession of First Nations’ people. It offers an invaluable insight into the ‘Aboriginal way of war’ and challenges the widespread perception that First Nation’s peoples were the passive victims of colonial expansion. The battle is the subject of a currently in-production documentary film with the working title The Battle of Meewah. For this documentary the filmmakers have developed a new approach to documentary film authorship that aligns more deeply with Indigenous story telling culture rather than the Western sole-authorship model.